Engineering of Saccharomyces cerevisiae for the accumulation of high amounts of triacylglycerol - Arhar, Simon (Microb Cell Fact, 2021)
BACKGROUND: Fatty acid-based substances play an important role in many products, from food supplements to pharmaceutical products and biofuels. The production of fatty acids, mainly in their esterified form as triacylglycerol (TAG), has been intensively studied in oleaginous yeasts, whereas much less effort has been invested into non-oleaginous species. In the present work, we engineered the model yeast Saccharomyces cerevisiae, which is commonly regarded as non-oleaginous, for the storage of high amounts of TAG, comparable to the contents achieved in oleaginous yeasts. RESULTS: We investigated the effects of several mutations with regard to increased TAG accumulation and identified six of them as important for this phenotype: a point mutation in the acetyl-CoA carboxylase Acc1p, overexpression of the diacylglycerol acyltransferase Dga1p, deletions of genes coding for enzymes involved in the competing pathways glycogen and steryl ester synthesis and TAG hydrolysis, and a deletion of CKB1, the gene coding for one of the regulatory subunits of casein kinase 2. With the combination of these mutations in a S. cerevisiae strain with a relatively high neutral lipid level already in the non-engineered state, we achieved a TAG content of 65% in the dry biomass. High TAG levels were not only obtained under conditions that favor lipid accumulation, but also in defined standard carbon-limited media. CONCLUSIONS: Baker's yeast, which is usually regarded as inefficient in the storage of TAG, can be converted into a highly oleaginous strain that could be useful in processes aiming at the synthesis of fatty acid-based products. This work emphasizes the importance of strain selection in combination with metabolic engineering to obtain high product levels. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12934-021-01640-0.